Antimicrobial photodynamic therapy alone or in combination with antibiotic local administration against biofilms of Fusobacterium nucleatum and Porphyromonas gingivalis - Tavares, Lívia J. [UNESP]; de Avila, Erica D. [UNESP]; Klein, Marlise I. [UNESP]; Panariello, Beatriz H.D.; Spolidório, Denise M.P. [UNESP]; Pavarina, Ana Cláudia [UNESP] (Elsevier, 2018)
Antimicrobial photodynamic therapy (aPDT) kills several planktonic pathogens. However, the susceptibility of biofilm-derived anaerobic bacteria to aPDT is poorly characterized. Here, we evaluated the effect of Photodithazine (PDZ)-mediated aPDT on Fusobacterium nucleatum and Porphyromonas gingivalis biofilms. In addition, aPDT was tested with metronidazole (MTZ) to explore the potential antimicrobial effect of the treatment. The minimum inhibitory concentration (MIC) of MTZ was defined for each bacterial species. Single-species biofilms of each species were grown on polystyrene plates under anaerobic conditions for five days. aPDT was performed by applying PDZ at concentrations of 50, 75 and 100 mg/L, followed by exposure to 50 J/cm 2 LED light (660 nm) with or without MTZ. aPDT exhibited a significant reduction in bacterial viability at a PDZ concentration of 100 mg/L, with 1.12 log 10 and 2.66 log 10 reductions for F. nucleatum and P. gingivalis in biofilms, respectively. However, the antimicrobial effect against F. nucleatum was achieved only when aPDT was combined with MTZ at 100× MIC. Regarding P. gingivalis, the combination of PDZ-mediated aPDT at 100 mg/L with MTZ 100× MIC resulted in a 5 log 10 reduction in the bacterial population. The potential antimicrobial effects of aPDT in combination with MTZ for both single pathogenic biofilms were confirmed by live/dead staining. These results suggest that localized antibiotic administration may be an adjuvant to aPDT to control F. nucleatum and P. gingivalis biofilms.
Keywords: Anaerobic bacteria; Combined modality therapy; Metronidazole; Photodynamic therapy